Needs Analysis of ESC (English Short Course) Program for Administrators in State Polytechnic Ambon - Yelliza, Ahmad (International Journal of English Education and Linguistics (IJoEEL), 2020)
English for Specific Purpose (ESP) refers to teaching and learning English as a foreign language for the purpose in using it in the certain domain.Â  The aimed of this study to wholly analyse the cornerstone of ESP focusing on needs analysis; necessities, wants and lacks. The study was conducted by using Research and Development (R&D), see Richey and Klein (2015). The data were obtained from questionnaires and interviews. Additionally, the results of needs analysis shown that English language needs of administrators majoring in daily conversation and English for profession (90 %) with various topics, then (20%) focusing on academic field. Furthermore, it was found that, there were 70% students as C2 (Basic-upper level) and 30% were C1 (Basic-lower level). Furthermore, schedule and difficulties in understanding materials were found as lacks for the administrators. In conclusion, the results of this study with suggestion for ESC program frequently instructors or teachers to design the syllabi and develop teaching materials related to the findings, and institution to issue the policy. It is strongly required do be done as soon as possible in order to support the State of Polytechnic Ambon becomes the best university in eastern Indonesia and can be a reference campus.Â Â